2010
DOI: 10.1007/s10493-010-9337-0
|View full text |Cite
|
Sign up to set email alerts
|

Tick burden on European roe deer (Capreolus capreolus)

Abstract: In our study we assessed the tick burden on roe deer (Capreolus capreolus L.) in relation to age, physical condition, sex, deer density and season. The main objective was to find predictive parameters for tick burden. In September 2007, May, July, and September 2008, and in May and July 2009 we collected ticks on 142 culled roe deer from nine forest departments in Southern Hesse, Germany. To correlate tick burden and deer density we estimated deer density using line transect sampling that accounts for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 43 publications
5
53
0
6
Order By: Relevance
“…Numerically, the mean infection rates in all ticks and adults decreased by 1.4% and 3.7%, respectively, whereas the infection rate in nymphs increased by 1.7% relative to the data given by Rauter and Hartung (21). We may hypothesize that this difference between the results of the metastudies could be caused by the recently increased involvement of ungulates (like deer or moose), which are generally considered transmission-incompetent hosts for B. burgdorferi sensu lato (34,35) but are frequent hosts of nymphal rather than larval I. ricinus ticks (36,37). An increase in the total abundance of I. ricinus ticks was associated with the abundance of large ungulates previously (15,25,38).…”
Section: Discussionmentioning
confidence: 69%
“…Numerically, the mean infection rates in all ticks and adults decreased by 1.4% and 3.7%, respectively, whereas the infection rate in nymphs increased by 1.7% relative to the data given by Rauter and Hartung (21). We may hypothesize that this difference between the results of the metastudies could be caused by the recently increased involvement of ungulates (like deer or moose), which are generally considered transmission-incompetent hosts for B. burgdorferi sensu lato (34,35) but are frequent hosts of nymphal rather than larval I. ricinus ticks (36,37). An increase in the total abundance of I. ricinus ticks was associated with the abundance of large ungulates previously (15,25,38).…”
Section: Discussionmentioning
confidence: 69%
“…Most of the examined animals (99.7%) harbored monospecific infestation by I. ricinus and only one roe deer presented double infestation I. ricinus/Dermacentor marginatus. The predominance of I. ricinus was also found by Carpi et al (2008), Skotarczac et al (2008 and Vor et al (2010) in roe deer from Italy, Poland and Germany, respectively, but not by Alonso et al (2004) in cervids from south-eastern Spain who found Boophilus annulatus and Rhipicephalus bursa as the dominant species, being I. ricinus one of the less prevalent.…”
Section: Discussionmentioning
confidence: 72%
“…Vor et al (2010) attributed the male biased tick parasitism found on whitetailed deer (Odocoileus virginatus) as an artefact of sexual size dimorphism. However, this explanation may not be valid for roe deer whose sexual dimorphism is less pronounced than white-tailed deer (Geist 1998), so the high prevalence detected in males would mean a higher contact with ticks possibly because of different feeding habits or habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tick species was collected for the first time from Capreolus capreolus. This tick-host association is often described in other European countries (Dautel et al 2006;Biadún et al 2007;Vor et al 2010), where the roe deer is common. In northern Portugal, however, this deer species Dark areas correspond to new records produced by tick surveillance program or recent bibliographic references (after 1994).…”
Section: The Genus Dermacentormentioning
confidence: 63%